Pelatihan Produksi Dodol Berbasis Nangka di Desa Tritis Yogyakarta - Cempaka, Laras; Asiah, Nurul (Indonesian Journal for Social Responsibility, 2019)
Tritis Village, Purwobinangun, Pakem, Sleman is one of the villages in the city of Yogyakarta which has a middle to lower economic level with the potential for garden produce in the form of abundant jackfruit, but with very cheap selling prices. Jackfruit Dodol is one of the processed food products that can be developed to increase the economic value of jackfruit. In this community service program, the community was given training in the development of jackfruit dodol products that were given innovations by adding beans as fillings and by making packaging designs that were different from the common dodol products on the market. The existence of jackfruit-based food processing training and product development innovation, is expected to be able to empower the potential of the resource and the community of Tritis Village. Furthermore, this product is expected to be able to become one of the typical food products by Yogyakarta, so that it has an impact on improving the economy of the people.